Relationship between Compliance and Effectivness of Tuberculosis Drugs in TB Patients - Sundari, Retno Tresno; Fadhilah, Yuke Nur; Ali, Taufik; Febiyanti, Dian; Roslina, Iis (Journal La Medihealtico, 2025)
Tuberculosis (TB) is an infectious disease caused by infection with Mycobacterium tuberculosis. Analyzing TB treatment compliance is crucial since TB therapy involves a lengthy course of treatment that might last up to six months without interruption. since one of the things that might help TB patients recover is compliance. The purpose of this study is to ascertain how drug usage efficacy and compliance relate to TB patients at Kedawung Health Center in the Cirebon Regency. This study employs a causal quantitative approach. 35 respondents who had received category 1 TB therapy and had completed at least two BTA sputum exams or supporting examinations (X-rays) made up the sample, which was selected using the purposive sampling strategy. the process of gathering compliance data using the MMAS-8 questionnaire and efficacy data (BTA sputum) using SITB software throughout the first, second, fifth, and/or sixth months of TB therapy. The chi square test was employed in the analysis. Findings High category (85.7%), moderate category (8.6%), and low category (5.7%) TB patients' adherence to TB medication usage. The efficacy of TB medication usage in patients with the effective (94.3%) and ineffective (5.7%) categories. Among TB patients, there is a high correlation between adherence and the efficacy of TB medication usage. At Kedawung Health Center, there is a strong correlation between compliance and sociodemographics regarding the duration of treatment for TB drug use in TB patients, as well as a strong correlation between effectiveness and sociodemographics regarding the duration of treatment for TB drug use in TB patients.